A comparative evaluation of Ficus religiosa with Ficus species for its anti-inflammatory activity: a review - Biju , C. R.; Jyotisree , G.; S., Amita; R., Sruthi (Creative Pharma Assent, 2020)
Herbal medicine is one of the oldest forms in medical treatment. Through various studies it was known that medicinal herbs are used for treating inflammatory disorders in traditional medicine. Inflammation is the body’s process of opposing against the foreign particles that harm it, such as infections, injuries etc. The work aims to compare the anti-inflammatory action of extracts of various Ficus species using Carrageenan induced hind paw oedema method and cotton pellet granuloma method. Literature surveys have been done to check the extent of anti-inflammatory activity on extracts of various plant parts like roots, leaves, barks, fruits etc. of Ficus species with oral administration of different doses. As a result, the leaf extract of plant Ficus religiosa have found to be greater effect compared to other Ficus species. Thus, the review may conclude that the anti-inflammatory effect of Ficus religiosa extract is more potent than other Ficus species